2019
DOI: 10.1007/s11469-019-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Emotional Maltreatment and Problematic Social Media Use Among Adolescents: The Mediating Role of Body Image Dissatisfaction

Abstract: Preliminary evidence suggests that childhood maltreatment is associated with higher problematic social media use (PSMU). It has also been established that childhood emotional maltreatment (CEM) is associated with body image dissatisfaction (BID). However, the direct and indirect impacts of CEM on PSMU via BID remain untested. The present study examined these direct and indirect relationships among a sample of 385 adolescents (mean age 15.62 years, range 14-18 years). Results indicated that female adolescents h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…Body Image Dissatisfaction Scale (BIDS) The unidimensional BIDS (Harter 2012) comprises five items (e.g., "I am not pleased with my physical appearance") on a 4-point Likert scale from "absolutely disagree" to "very true" that assess the dissatisfaction levels of adolescents with their body image. The Turkish adaptation with the adolescent sample indicated good structural validity (χ 2 /df = 2.47, RMSEA = .06 [CI 90% (.00, .13)], SRMR = .03, CFI = .99, GFI = .99) of the scale (Kircaburun et al 2018c). The internal consistency was high in the present study (α = .85).…”
Section: Methodsmentioning
confidence: 96%
“…Body Image Dissatisfaction Scale (BIDS) The unidimensional BIDS (Harter 2012) comprises five items (e.g., "I am not pleased with my physical appearance") on a 4-point Likert scale from "absolutely disagree" to "very true" that assess the dissatisfaction levels of adolescents with their body image. The Turkish adaptation with the adolescent sample indicated good structural validity (χ 2 /df = 2.47, RMSEA = .06 [CI 90% (.00, .13)], SRMR = .03, CFI = .99, GFI = .99) of the scale (Kircaburun et al 2018c). The internal consistency was high in the present study (α = .85).…”
Section: Methodsmentioning
confidence: 96%
“…The scale includes 10 items measuring adolescents' knowledge and competencies to promote health. The responses were computed to a sum score, which was then recoded into three categories: low health literacy (values 10-25), medium health literacy (values [26][27][28][29][30][31][32][33][34][35], and high health literacy (values 36-40) [44]. Academic achievement was measured by asking students to indicate their most recent mark in the school subjects first language and mathematics.…”
Section: Methodsmentioning
confidence: 99%
“…Following a longitudinal study, Vannucci and Ohannessian [ 27 ] reported that “social media patterns appear to differentially predict psychosocial adjustment during early adolescence, with high social media use being the most problematic”. Problematic social media use has been linked to a greater likelihood of depressive symptoms [ 5 , 9 , 22 , 28 , 29 , 30 , 31 , 32 ], anxiety [ 28 , 32 ], lower self-esteem [ 9 , 28 , 32 ], social isolation [ 29 ], lower life-satisfaction [ 18 ], poorer sleep quality [ 21 , 28 , 32 ], disordered eating [ 33 ], and higher body image dissatisfaction [ 34 ]. Considering the associations with the various psychosomatic complaints, it is easy to understand why assessment of social media use has been proposed as a standard element in psychiatric assessment [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students were primarily white (63%), black (22%), and Asian (15%), with an almost even gender split (48%/52% female/male), and from diverse socio-economic communities: Upper socio-economic class (20%), middle class (54%), and lower class (26%). The study targeted adolescents due to the: (i) high online usage this age group exhibits, and the vulnerability to peer evaluations and risk behaviors [39], (ii) heightened vulnerability to excessive online use, leading potentially to addictive symptoms [40], and (iii) development of body-image concerns and an overemphasis on peer comparisons that may be associated with the development of eating disorders and obesity [41,42,43].…”
Section: Methodsmentioning
confidence: 99%